A Sceptic's Guide to Justice in International Tax Policy. Issue 2 (August 2019) - van Apeldoorn, Laurens
Abstract: What, if any, are the moral norms governing the international taxation regime if the sceptic is right to think that considerations of distributive justice do not apply beyond the state? I sketch an answer to this question by examining Tsilly Dagan's illuminating recent book International Tax Policy: Between Competition and Cooperation. In her work, Dagan identifies the position of Thomas Nagel, an influential global justice sceptic, as predominant among commentators in legal scholarship and policy debates on international taxation. According to Nagel, multilateral cooperation is appropriately conceived as a bargain between mutually self-interested states. In tracing the implications of his position for international tax policy Dagan argues that even a sceptic like Nagel is committed to identifying some considerations of distributive justice beyond the state to ameliorate the harmful effects of tax competition. In response I argue that Dagan is correct to claim that the global justice sceptic is committed to seeing cooperation in international tax policy as constrained by moral norms, but that these norms are what Nagel calls humanitarian duties rather than duties of justice. I establish that Dagan's argument that Nagel is committed to a duty of justice to promote distributive justice abroad faces some significant obstacles and suggest that Dagan can ground her argument in a humanitarian duty that Nagel does accept. The upshot of the argument is that even if the sceptic is right to think that considerations of distributive justice do not apply beyond the state, multilateral tax cooperation is governed by a duty of states to prevent human rights deficits where they can.